2020
DOI: 10.1002/ece3.6571
|View full text |Cite
|
Sign up to set email alerts
|

From leaf to label: A robust automated workflow for stomata detection

Abstract: Plant leaf stomata are the gatekeepers of the atmosphere–plant interface and are essential building blocks of land surface models as they control transpiration and photosynthesis. Although more stomatal trait data are needed to significantly reduce the error in these model predictions, recording these traits is time‐consuming, and no standardized protocol is currently available. Some attempts were made to automate stomatal detection from photomicrographs; however, these approaches have the disadvantage of usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…Recent studies have demonstrated that deep learning approaches can be used to quantify microscopic but important phenotypes such as the density and/or shape of stomata in a range of plant species [ 12 17 ]. Quantification of hairiness has been attempted in Arabidopsis thaliana , Soybean ( Glycine max ) and Spring Wheat ( Triticum aestivum ) [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that deep learning approaches can be used to quantify microscopic but important phenotypes such as the density and/or shape of stomata in a range of plant species [ 12 17 ]. Quantification of hairiness has been attempted in Arabidopsis thaliana , Soybean ( Glycine max ) and Spring Wheat ( Triticum aestivum ) [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stomata analysis serves as a basic example of instance segmentation. Despite several previous works on the automated examination of stomata (Toda et al, 2018;Fetter et al, 2019;Li et al, 2019;Carrasco et al, 2020;Casado-García et al, 2020;Meeus et al, 2020;Song et al, 2020), this contribution, to our knowledge, is the first trying to automatically segment whole stomata (represented by their guard cells) With the presented exemplary analyses, we hope to provide guidance for the application of GinJinn2 for automatic data collection and feature extraction. Despite GinJinn2's progress compared to its predecessor, there is still room for further improvements.…”
Section: Discussionmentioning
confidence: 99%
“…The stomata analysis serves as a basic example of instance segmentation. Despite several previous works on the automated examination of stomata (Carrasco et al, 2020;Casado-García et al, 2020;Fetter et al, 2019;Li et al, 2019;Meeus et al, 2020;Song et al, 2020;Toda et al, 2018), this contribution, to our knowledge, is the first trying to automatically segment whole stomata (represented by their guard cells) using deep learning. With only 88 highly variable training images, our model achieved an AP of 51.32.…”
Section: Discussionmentioning
confidence: 99%